2016
DOI: 10.1088/0953-4075/49/19/195202
|View full text |Cite
|
Sign up to set email alerts
|

Ionisation differential cross section measurements for N2at low incident energy in coplanar and non-coplanar geometries

Abstract: Abstract.Ionization triple differential cross sections (TDCS) have been determined experimentally and theoretically for the neutral molecule N 2 over a range of geometries from coplanar to the perpendicular plane. Data were obtained at incident electron energies ~10 eV and ~20 eV above the ionization potential (IP) of the 3σ g , 1π u and 2σ g states, using both equal and non-equal outgoing electron energies. The data were taken with the incident electron beam in the scattering plane (ψ = 0°), at 45° to this pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…We used two theoretical methods to describe the present electron-impact ionization process. Although they have been described previously [35][36][37][38] we summarize the essential ideas and the particular ingredients for the current cases of interest in order to make this paper self-contained. More detailed information can be found in the references given.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…We used two theoretical methods to describe the present electron-impact ionization process. Although they have been described previously [35][36][37][38] we summarize the essential ideas and the particular ingredients for the current cases of interest in order to make this paper self-contained. More detailed information can be found in the references given.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…This doubly-symmetric geometry is particularly challenging, since under these conditions the TDCS is highly sensitive to both initial and final states of the system. In the previous work [17] it was found that the models did not predict the data well for the lowest energy studied ( E 1 = E 2~5 eV ), however as the energy was raised to E 1 = E 2 = 20 eV , better agreement was found in the overall shape of the calculated cross sections. It was suggested that further work was needed, including measurements at higher energies to establish if the models improved under these conditions.…”
Section: Figmentioning
confidence: 76%
“…In a previous set of experiments carried out in Manchester, TDCS data were obtained for ionization of N 2 in a doubly-symmetric geometry, where both electron detectors were set so that θ 1 = θ 2 and E 1 = E 2 . These results were compared to calculations from the Missouri group of Don Madison and co-workers [17]. This doubly-symmetric geometry is particularly challenging, since under these conditions the TDCS is highly sensitive to both initial and final states of the system.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations